Colonialism as an Education System. The Case of Brazil - Paulo Freire's Home Country - Hanna Kostyło (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
The valuable life of individuals and communities built by them is a purpose which is commonly considered as desired. Are we able to educate the youth accordingly? Is education of that kind possible at all in today's world? The situation of postcolonial countries is particularly interesting in that context. Societies of those countries, weighed down by the domination of culturally foreign invaders, have been internally broken. This is the case of Brazil, Paulo Freire's home country. In his classic work, Pedagogy of the Oppressed, Freire undertakes the question of the situation of the Brazilian society after the abolishment of colonialism in the 1960s. In this text, after presenting the main concepts and the historical and social backgrounds of the said transformation, I will focus on the limitations embedded in the Brazilian post-colonized people which do not allow them to create valuable life for themselves, both as individuals and communities. I will show in which way colonialism destroys values on the both levels.